2021
DOI: 10.1126/sciadv.abf5632
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the cross-neutralization of SARS-CoV and SARS-CoV-2 by the human monoclonal antibody 47D11

Abstract: The emergence of SARS-CoV-2 antibody escape-mutations highlights the urgent clinical need for broadly neutralizing therapeutics. We previously identified a potent human monoclonal antibody, 47D11, capable of cross-neutralizing SARS-CoV-2 and SARS-CoV, and protecting against the associated respiratory disease in an animal model. Here, we report cryo-EM structures of trimeric SARS-CoV and SARS-CoV-2 spike ectodomains in complex with the 47D11 Fab. 47D11 binds specifically to the closed conformation of the recept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 103 publications
(166 reference statements)
0
60
0
Order By: Relevance
“…This Ab was generated from H2L2 human Ab transgenic mice, which were immunized with the S ectodomain of HCoV-OC43, SARS-CoV, and MERS-CoV. Cryo-EM structures showed that 47D11 binds specifically to the closed conformation of the RBD, distal to the ACE2 binding site [ 67 ]. Interestingly, 47D11 preferentially recognizes the partially open conformation of the SARS-CoV-2 S protein, suggesting that it could be used effectively in combination with other Abs that target the exposed RBM.…”
Section: Therapeutic Absmentioning
confidence: 99%
“…This Ab was generated from H2L2 human Ab transgenic mice, which were immunized with the S ectodomain of HCoV-OC43, SARS-CoV, and MERS-CoV. Cryo-EM structures showed that 47D11 binds specifically to the closed conformation of the RBD, distal to the ACE2 binding site [ 67 ]. Interestingly, 47D11 preferentially recognizes the partially open conformation of the SARS-CoV-2 S protein, suggesting that it could be used effectively in combination with other Abs that target the exposed RBM.…”
Section: Therapeutic Absmentioning
confidence: 99%
“…Six monoclonal antibodies that cross-reacted with the S proteins of SARS-CoV, SARS-CoV-2, and other coronaviruses via diverse epitopes were identified [ 91 ]. Human monoclonal antibody (mAb) 47D11 can specifically recognize the downward conformation of the viral RBD by targeting the conserved hydrophobic pocket in the RBD of SARS-CoV and SARS-CoV-2, and thus capturing these two viruses in a completely closed and a partially open conformation, respectively [ 92 ]. The neutralization efficiency of 47D11 is not affected by the mutations in the RBM (receptor binding motif), such as K417N, E484K, or N501Y, which makes 47D11 a promising therapeutic candidate against the new and rapidly spreading SARS-CoV-2 and its variants [ 92 ].…”
Section: Targets For Pan-coronavirus Vaccinesmentioning
confidence: 99%
“…Human monoclonal antibody (mAb) 47D11 can specifically recognize the downward conformation of the viral RBD by targeting the conserved hydrophobic pocket in the RBD of SARS-CoV and SARS-CoV-2, and thus capturing these two viruses in a completely closed and a partially open conformation, respectively [ 92 ]. The neutralization efficiency of 47D11 is not affected by the mutations in the RBM (receptor binding motif), such as K417N, E484K, or N501Y, which makes 47D11 a promising therapeutic candidate against the new and rapidly spreading SARS-CoV-2 and its variants [ 92 ]. Further research shows that 47D11 can effectively neutralize ACE2-dependent betacoronaviruses, such as SARS-CoV, SARS-CoV-2, and the SARS-like bat betacoronavirus, WIV16 [ 92 ].…”
Section: Targets For Pan-coronavirus Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, to set an appropriate baseline for the Spike-Furin interaction in SARS-CoV-2, a second round of docking was performed by taking the same ligand (Furin: 1P8J) and docking it onto the representative homologous Spike structure (PDB ID: 7AKJ) [58] of SARS-CoV (2002. This cryo EM structure was solved in the process of exploring 'the convalescent patient sera option' for the then seemed possible prevention and treatment of COVID-19, as a natural extension of SARS [59].…”
Section: Details and Rationales Of Experimental Structural Templates Used For Docking And Dynamicsmentioning
confidence: 99%